Clinical and virological outcomes with baloxavir compared with oseltamivir in pediatric patients aged 6 to < 12 years with influenza: an open-label, randomized, active-controlled trial protocol - Ishiguro, Nobuhisa; Morioka, Ichiro; Nakano, Takashi; Furukawa, Masashi; Tanaka, Shintaro; Kinoshita, Masahiro; Manabe, Atsushi (BMC infectious diseases, 2021)
Children with influenza virus infections are prone to complications and are common sources of influenza transmission. Baloxavir marboxil inhibits cap-dependent endonuclease and was approved for influenza treatment in adolescent, adult, and pediatric patients in Japan. The miniSTONE-2 study included pediatric patients with influenza (1 to < 12 years) and demonstrated similar median times to alleviation of signs and symptoms of influenza with a single dose of baloxavir granules (weight < 20 kg: 2 mg/kg, [greater than or equai to] 20 kg: 40 mg) and oseltamivir. Although the baloxavir dose in miniSTONE-2 was higher than the Japanese-approved dose, baloxavir exposure in miniSTONE-2 was similar to Japanese pediatric patients who receive the Japanese-approved dose. This study will be the first randomized active-controlled study in pediatric patients with influenza using the Japanese-approved dose of baloxavir. This is a multicenter, open-label, randomized, active-controlled trial in which 200 Japanese subjects aged 6 to < 12 years with influenza virus infection are randomly allocated (2:1) to a single dose of baloxavir at the approved dose in Japan (weight [greater than or equai to] 10 to < 20 kg: 10 mg, [greater than or equai to] 20 to < 40 kg: 20 mg, [greater than or equai to] 40 kg: 40 mg) or oseltamivir twice daily for 5 days. The primary clinical endpoint is the time to illness alleviation of influenza, from administration of baloxavir or oseltamivir until the following criteria were met and sustained for at least 21.5 h (24 h--10%): cough and nasal discharge/nasal congestion rated as absent or mild axillary body temperature < 37.5 [degrees]C. The primary analysis population is the intention-to-treat infected population, which includes all pediatric subjects who receive at least one dose of study drug and have confirmed influenza virus infection by reverse transcription-polymerase chain reaction. The safety population includes all subjects who receive at least one dose of study drug. No comparative studies have been conducted to confirm the efficacy and safety of baloxavir versus a comparator in pediatric patients with influenza infection in Japan. The outcomes from this trial will provide evidence on the efficacy and safety of baloxavir as an antiviral treatment option for Japanese pediatric patients with influenza infection. Trial registration Japan Registry of Clinical Trials: jRCTs011200011. Registered November 2020. (https://rctportal.niph.go.jp/en/).